You Push the First valve Down - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "You Push the First valve Down," written by Walter B. Wriston for the Fellows of the Academy of International Business on 18 October 1985. The original speech is located in MS134.001.007.00001.